Demographic Analysis of Urban Consumers’ Fruit Salad Preferences in Malang City, East Java of Indonesia - Noor, Arif Yustian Maulana; Isaskar, Riyanti; Ummah, Khoirul; Fitri, Kanissa Gita (HABITAT, 2025)
Urban consumers are increasingly exposed to health risks and dietary transitions, prompting growing interest in organic food products. However, actual purchasing behavior for organic options, such as fruit salad, remains inconsistent, particularly in emerging economies. Existing studies tend to emphasize attitudinal factors in developed markets, leaving a gap in understanding how structural demographic attributes influence organic preferences in developing urban contexts. This study aims to examine how education, marital status, income, gender, expenditure, and buying frequency shape consumer preference for organic fruit salad. A cross-sectional survey was conducted in an urban Indonesian setting, and binary logistic regression was employed to identify significant predictors. The results reveal that education and marital status are strong positive determinants of organic preference, while monthly expenditure is marginally significant. In contrast, income, gender, and buying frequency show no statistically significant effects. These findings suggest that informational access, household responsibility, and food budgeting behavior better explain organic food choices than income or habitual purchasing. The study contributes to consumer behavior and food preference literature by highlighting the socio-demographic foundations of sustainable consumption. Implications are offered for urban nutrition policy, consumer segmentation strategies, and targeted marketing to support the adoption of organic food in middle-income societies.